PENGARUH STRUKTUR AUDIT, TEKANAN WAKTU, DISIPLIN KERJA DAN KOMITMEN ORGANISASI PADA KINERJA AUDITOR - Putri Gayatri, Komang Dyah; Dharma Suputra, I Dewa Gde (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of the structure of audit, time pressure, work discipline and organizational commitment to the performance of auditors. This research was conducted in the Office of Public Accountant registered at Indonesian Institute of Accountants (IAPI) area of ??Bali in 2015. The samples were selected using purposive sampling so that the sample used in the study were 43 auditors. Data obtained by distributing questionnaires to auditors and analysis techniques used were multiple linear regression. Based on the results of analysis show that the structure of the audit, work discipline, and organizational commitment and significant positive effect while the pressure of time does not affect the performance of the auditor in public accounting firm in the province of Bali.
Keywords: audit structure, pressure time, work discipline, organizational commitment, performance auditor